Transcription Regulation—Brain Development and Homeostasis—A Finely Tuned and Orchestrated Scenario in Physiology and Pathology - Muñoz, Estela Maris (2021)
A finely tuned regulation of gene expression is essential for shaping the nervous system and for maintaining its homeostasis throughout life. Disruptions in gene regulation can impact brain development and physiology in ways that contribute to diverse pathologies. Classic and state-of-the art experimental models and technologies have advanced our knowledge of transcriptional regulators and the ways they interact in the healthy and diseased brain. Further in-depth characterization of the mechanisms of transcriptional regulation is needed to better understand how each element, from genes to cells, defines and maintains identities and functionalities in the nervous system. This Research Topic focuses on transcriptional regulation within the nervous system, with an emphasis on developmental and homeostatic processes, their dysregulation, and their association with neurodevelopmental disorders and neurodegenerative diseases. Eleven peer-reviewed manuscripts including six original articles, three reviews, one mini review, and one brief research report, encompass this special volume. Fifty-nine authors from research laboratories located in 10 countries: Argentina, Canada, China, Germany, Israel, Russia, Serbia, United Kingdom, United States, and Vietnam, took part in this initiative.